2002
DOI: 10.1063/1.1481196
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced nitrogen incorporation by pulsed laser annealing of GaNxAs1−x formed by N ion implantation

Abstract: We demonstrate that pulsed laser annealing followed by rapid thermal annealing greatly enhances incorporation of substitutional N in N + -implanted GaAs. Films implanted to 1.8% N exhibit a fundamental band gap of 1.26eV (a band gap reduction of 160meV), corresponding to an N activation efficiency of 50%. The optical and crystalline quality of the synthesized film is comparable to GaN x As 1-x thin films of similar composition grown by epitaxia l growth techniques. Compared to films produced by N + implantatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 20 publications
0
25
0
Order By: Relevance
“…Compared to films produced by N + implantation and rapid thermal annealing only, the introduction of PLM improves N incorporation by a factor of five. It was found that subsequent RTA at temperatures higher than ~700ºC after PLM was essential in obtaining good quality GaN x As 1-x thin films with clear optical transitions [26]. The optical properties and crystalline quality of these films are comparable to GaN x As 1-x thin films of similar composition made by epitaxial growth techniques.…”
Section: Nitrogen Activation Efficiencymentioning
confidence: 64%
See 1 more Smart Citation
“…Compared to films produced by N + implantation and rapid thermal annealing only, the introduction of PLM improves N incorporation by a factor of five. It was found that subsequent RTA at temperatures higher than ~700ºC after PLM was essential in obtaining good quality GaN x As 1-x thin films with clear optical transitions [26]. The optical properties and crystalline quality of these films are comparable to GaN x As 1-x thin films of similar composition made by epitaxial growth techniques.…”
Section: Nitrogen Activation Efficiencymentioning
confidence: 64%
“…In a previous report, we demonstrated that pulsed laser melting followed by rapid thermal annealing (PLM-RTA) greatly enhanced the incorporation of substitutional N in N + -implanted GaAs [26]. Films implanted with 1.8% N exhibited a fundamental band gap of 1.26eV (a band gap reduction of 160meV), corresponding to an N activation efficiency of ~50%.…”
Section: Nitrogen Activation Efficiencymentioning
confidence: 99%
“…The highest reported As content in MOVPE grown layers is x~0.067 [10,11,12]. Even lower maximum As contents of x~0.0026 [19] and x~0.01 [20] were achieved in MBE layers grown at .750 o C and at 500 o C, respectively Recently, materials with constituents having drastically different chemical or physical properties at compositions or structures far exceeding their thermodynamic solubility and stability limits have been synthesized using extreme non-equilibrium synthesis techniques [21,22,23]. The atomic diffusion length in these non-equilibrium processes is long enough to form crystalline lattices with uniform compositions, but short enough to avoid equilibrium phase segregation.…”
Section: Low Temperature Molecular Beam Epitaxial Growth Of Ga-n-asmentioning
confidence: 99%
“…For both techniques, it is difficult to obtain a high concentration of As in the alloy before phase separation occurs. The 6 highest reported As content in MOVPE grown layers is x~0.067 [10,11,12] [21,22,23]. The atomic diffusion length in these non-equilibrium processes is long enough to form crystalline lattices with uniform compositions, but short enough to avoid equilibrium phase segregation.…”
mentioning
confidence: 99%
“…The combined ion 3 beam and laser processing approach has been demonstrated as an effective approach to synthesize dilute semiconductor alloys including GaN x As 1-x [9,10] and Ga 1-x Mn x As [11].…”
Section: Introductionmentioning
confidence: 99%